Analyzing Public Interest in Metabolic Health-Related Search Terms During COVID-19 Using Google Trends - McCarthy, Alec D (Cureus, 2021)
Background In late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged as a novel virus and initiated a series of events that culminated in the global coronavirus disease 2019 (COVID-19) pandemic. Throughout 2020 and the first half of 2021, massive investigational efforts towards identifying, treating, preventing, and slowing the spread of COVID-19 were carried out. Several predictors for clinical outcomes relating to metabolic health were identified. Aim and methods This study aimed to investigate how public interest in search terms associated with metabolic health has changed throughout and during the course of the COVID-19 pandemic. Google Trends was utilized as a tool to gather and compare public interest data in a variety of search phrases. The relative search values were plotted over time, compared pre-and post-COVID-19, analyzed for correlation, assessed for trend directionality, and checked for trend inclusion. Results The public interest measured by relative search volume in “metabolic health,” “exercise,” “home exercise," “health,” and “how to improve fitness” significantly increased from pre- to post-COVID-19 pandemic onset while “diet” and “fitness” significantly decreased. The search terms “COVID” and “coronavirus” made up more than 95% of screen queries incorporating COVID-19. During the COVID-19 pandemic, “diabetes” and “weight loss” had the most significant increases in search volume. Conclusions Given the changes in public interest observed throughout the course of the COVID-19 pandemic, it is clear that the association between metabolic health and COVID-19 is being successfully disseminated to the public. However, these changes also warrant increased public education surrounding diet and fitness to align public interest with measures proven to improve the clinical outcomes of COVID-19.